MISI PROPETIK PENDIDIKAN ISLAM: MEMBENTUK KARAKTER MENUJU TRANSFORMASI SOSIAL MEMBANGUN PERADABAN - Ahmad, Askar (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: The high civilization will be achievedÂ  ifÂ  humans are able to transform themselves as the capital for social transformation, while the social transformation will occur if humans have a strong character and personality to deal with the dynamics of the times. The prophetic mission of Islamic education is to educate people to have a noble character or prophetic consciousness, that is the awareness to build an advanced and civilized life, upholding the universal human principles based on the pure and strong theological ethics, and developing science and technology which ensures the continuity of human civilization.Kata Kunci: karakter, transformasi sosial, kemajuan dan peradaban Â